Christians and Churches: A History of Challenges and Diversities - Araya Guillén, Victorio (2022)
The text presents the Christianities as a broad set of diverse traditions or ecclesial movements that have been built and are still being built throughout its complex world historical evolution of more than twenty centuries. Speaking in the plural, the author argues that in the historical and social reality there are Christianities that are not only diverse, but also opposed, developed in very different cultural and ecclesial contexts. In this way, the churches must also be considered in their diversities, to recognize and respect the rich plurality manifested in polymorphous institutional structures, liturgical celebrations, and confessional expressions and magisterial.